1983
DOI: 10.3382/ps.0622169
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella and Other Enterobacteriaceae Found in Commercial Poultry Feed

Abstract: Poultry feed (mash and pelleted) and meat and bone meal samples were collected from commercial mills. All samples were analyzed for Enterobacteriaceae count (ENT) and Salmonella. The genus and species of the various Enterobacteriaceae present were also determined. The average ENT for mash, pelleted, and meal samples was log 4.1, .8, and 1.8/g, respectively. Enterobacteriaceae were present in 100, 60, and 92% and Salmonella in 58, 0, and 92% of the mash, pelleted, and meal samples, respectively. Overall, the En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
3

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 13 publications
0
33
0
3
Order By: Relevance
“…Although results are highly variable, depending on the temperature and moisture content of pellets, in most studies pelleted feeds are less contaminated than mash feeds. Cox et al (1983) detected Salmonella in 58% of mash feed samples compared to zero per cent in pelleted feed samples. Pelleting, however, does not preclude Salmonella contamination of the finished products.…”
Section: Feed Decontaminationmentioning
confidence: 93%
“…Although results are highly variable, depending on the temperature and moisture content of pellets, in most studies pelleted feeds are less contaminated than mash feeds. Cox et al (1983) detected Salmonella in 58% of mash feed samples compared to zero per cent in pelleted feed samples. Pelleting, however, does not preclude Salmonella contamination of the finished products.…”
Section: Feed Decontaminationmentioning
confidence: 93%
“…The Salmonella isolation rate in this surveillance was not as high as that reported by Cox et al [2], Veldman et al [16] and Davies and Wray [3]. Davies and Wray [3] reported that S. Enteritidis was isolated on one occasion from an intake pit spillage but not from any bagger ones in a feed mill which 26 serovars of Salmonella were frequently isolated.…”
mentioning
confidence: 49%
“…Davies and Wray [3] reported that S. Enteritidis was isolated on one occasion from an intake pit spillage but not from any bagger ones in a feed mill which 26 serovars of Salmonella were frequently isolated. Whilst Cox et al [2] or Veldman et al [16] did not S. Enteritidis from any feeds. The Salmonella isolation rate from feed samples seems to relate to that from eggs in this area (unpublished data).…”
mentioning
confidence: 99%
“…These vectors, in turn, could be responsible for perpetuating Salmonella transmission among birds. Feed and feeder contents have been reported as major sources of horizontal transmission of Salmonella in poultry houses (MacKenzie and Bains, 1976;Cox et al, 1983;Jones et al, 1991). McIlroy (1998) reported that about 15% of feed samples tested positive for Salmonella.…”
Section: Frequency Of Detectionmentioning
confidence: 98%